2011
DOI: 10.1111/j.1365-2818.2011.03500.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological properties of Ag2SeTe nano thin films prepared by thermal evaporation

Abstract: SummarySemiconducting silver selenide telluride (Ag 2 SeTe) thin films were prepared with different thicknesses onto glass substrates at room temperature using thermal evaporation technique. The structural properties were determined as a function of thickness by X-ray diffraction exhibiting no preferential orientation along any plane; however, the films are found to have peaks corresponding to mixed phase. The morphology of these films was studied using scanning electron microscope and atomic force microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…5(f) represents the SEM micrograph of (Se 80 Te 20 ) 96 Ag 4 ultra-thin films annealed between T g and T c . The existence of stone-like crystals of different shapes that may be attributed to the formation of Ag 2 Se or Ag 2 Te nanophases alone or collectively in Se-Te-Ag thin films is also reported by many researchers [37][38][39]. The quantity B −1 measures the extent of band tailing into the band gap of the amorphous semiconductors for a given material.…”
Section: Compositionmentioning
confidence: 82%
“…5(f) represents the SEM micrograph of (Se 80 Te 20 ) 96 Ag 4 ultra-thin films annealed between T g and T c . The existence of stone-like crystals of different shapes that may be attributed to the formation of Ag 2 Se or Ag 2 Te nanophases alone or collectively in Se-Te-Ag thin films is also reported by many researchers [37][38][39]. The quantity B −1 measures the extent of band tailing into the band gap of the amorphous semiconductors for a given material.…”
Section: Compositionmentioning
confidence: 82%
“…The formation of the bulk Ag 2 Se 0·2 Te 0·8 compound at room temperature has been confirmed by X-ray powder diffraction analysis and reported. 1 Figures 1–3 show the typical XRD patterns of thermally evaporated Ag 2 Se 0·2 Te 0·8 films of thicknesses of 50, 95 and 230 nm respectively. In this paper, the Pearson's XRD standard for bulk is taken as reference for the XRD analysis of ternary thin films.…”
Section: Resultsmentioning
confidence: 99%
“…Ag2SeTe are interesting semiconducting ternary system having potential application in energy storage devices, photosensitisers, magneto-optic sensing devices, etc. 1,2 Synthesis, characterisation, optimisation and designing a manufacturing process of such systems in nanothin film form are of paramount interest recently owing to the need for storage and sensing devices. Several authors have reported on the manufacturing of thin films for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…These needle‐like grains tend to agglomerate. When the thermal energy is not sufficient, further agglomeration and the neighboring layers cohesive force toward the substrate dominate during which the film being before crystallized leads to the needle‐like morphology (Vijayan et al, ).…”
Section: Resultsmentioning
confidence: 99%